Picture Book Series as A Medium to Foster Reading Interest of Madrasah Ibtidaiyah Children - Khikmah, Nur; Ningsih, Tutuk (International Proceedings of Nusantara Raya, 2023)
Indonesian people's reading interest, especially for MI/SD children, is still relatively low because they prefer playing online games, watching television, etc. This factor causes their reading ability is still lacking. In addition, there are reading books (both story books and textbooks) in school institutions which are still monotonous with colorless pictures so that children get bored easily and are not interested in reading them. Based on the phenomenon above, the teacher's interest in reading in MI/SD children must be increased because "books are a storehouse of knowledge and reading can open the horizons of the world". The use of learning media to foster children's reading interest is by using a series of picture books. This series of picture books is more developed if the teacher dares to be creative by making colorful pictures accompanied by simple sentences that can attract children's interest in reading them. This series of picture books is effectively used in the learning of MI/SD children because they contain games as well as education. In a series of picture books there are several learning activities including observing, telling, reading and sorting the pictures so that they become a complete story. Furthermore, the teacher can add/collaborate on strategies or methods that can support the use of picture book series to be more innovative in each lesson.